An evaluation of key working for families of children and young people with special educational needs and disabilities. (29th July 2015) - Mengoni, Silvana; Bardsley, Janet; Oates, John
Abstract : Key working is a way of supporting children and young people with special educational needs and disabilities (SEND) and their families, and is highly regarded by families and practitioners. However, there is a lack of up‐to‐date research exploring key working in the current context of policy reforms in England. This article reports an evaluation of key working in four sites in England, with a particular focus on the SEND policy reforms. Key working resulted in a number of positive outcomes for children and young people, families and services, including helping services to meet the requirements of the SEND reforms. Challenging aspects included managing transitions and the relationship between key working practitioner and family, but successful strategies were identified. Key working supports the implementation of specific aspects of the English SEND reforms along with more general cultural change in services to align with families' needs and well‐established aspects of good practice.